Changes in diabetes medication regimens and glycemic control in adolescents and young adults with youth‐onset type 2 diabetes: The SEARCH for diabetes in youth study. Issue 6 (13th June 2018) - Pinto, Cathy A; Stafford, Jeanette M; Wang, Tongtong; Shankar, R Ravi; Lawrence, Jean M; Kim, Grace; Pihoker, Catherine; D'Agostino, Ralph B; Dabelea, Dana
Abstract : Objective: The aim of this study was to describe recent medication patterns and changes in medication patterns and glycemic control in adolescents and young adults with incident type 2 diabetes (T2D). Methods: Using data from the SEARCH for Diabetes in Youth Study, we conducted a cross‐sectional analysis of treatments for adolescents and young adults with incident T2D in 2 periods (2002‐2005 vs 2008/2012), and a longitudinal analysis of medications and glycemic control for a subset with baseline and follow‐up visits. Comparisons were performed using χ 2, Fisher's exact, or ANOVA. Results: Of 646 individuals in the cross‐sectional analysis, a majority in each period received metformin (64.9% vs 70.4%) and/or insulin (38.1% vs 38.4%), while fewer used sulfonylureas (5.6% vs 3.6%) with non‐significant changes over time. There was a significant reduction in thiazolidinedione use (5.0% vs 2.0%, P < .05). In the longitudinal analysis, 322 participants were followed for 7 years, on average. Baseline metformin users had a lower A1C (6.4% [46.7 mmol/mol]) compared to insulin (8.4% [68.2 mmol/mol], P < .001) or insulin plus any oral diabetes medication (ODM) users (7.7% [60.4 mmol/mol], P < .001). Among baseline metformin users ( n = 138), 29.7% reported metformin at follow‐up, with the remainder adding (19.6%) or switching to insulin (8.0%), ODM (15.9%), or lifestyle only (26.8%). Of those receiving insulin (±ODM) ( n = 129), 76% reported insulin use at follow‐up. Overall, 35% were at A1C goal (<7.0%, 53 mmol/mol) at follow‐up. Conclusions: Youth‐onset T2D is still largely being treated with metformin and/or insulin. The majority treated were not at American Diabetes Association (ADA)‐recommended goal 7 years after diagnosis.